2018
DOI: 10.1016/j.clim.2018.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and molecular features of X-linked hyper IgM syndrome – An experience from North India

Abstract: X-linked hyper IgM Syndrome (XLHIGM), the most frequent form of the Hyper IgM syndromes is a primary immune deficiency resulting from a mutation in the CD40 ligand gene (CD40LG). We analyzed the clinical and laboratory features of ten patients with XLHIGM, who were diagnosed at a tertiary care hospital in North India. Most common infections were sinopulmonary infections (80%) and diarrhea (50%). Sclerosing cholangitis and necrotising fasciitis were noted in one patient each. Three novel mutations in CD40LG (c.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 27 publications
2
10
0
Order By: Relevance
“…Apart from opportunistic infections, a number of PIDs are thought to be susceptible to mycobacterial disease; these include severe combined immunodeficiency (SCID), chronic granulomatous disease (CGD), Mendelian susceptibility to mycobacterial diseases, hyperimmunoglobulin E syndrome (HIES) and XHIM. This is particularly true in countries in which neonatal BCG vaccination is mandatory (eg, China, India and Latin America ) . In our cohort, almost all patients suffered local adverse events following vaccination with BCG; these included swelling or ulcerations >10 mm at the vaccination site.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Apart from opportunistic infections, a number of PIDs are thought to be susceptible to mycobacterial disease; these include severe combined immunodeficiency (SCID), chronic granulomatous disease (CGD), Mendelian susceptibility to mycobacterial diseases, hyperimmunoglobulin E syndrome (HIES) and XHIM. This is particularly true in countries in which neonatal BCG vaccination is mandatory (eg, China, India and Latin America ) . In our cohort, almost all patients suffered local adverse events following vaccination with BCG; these included swelling or ulcerations >10 mm at the vaccination site.…”
Section: Discussionmentioning
confidence: 89%
“…This is particularly true in countries in which neonatal BCG vaccination is mandatory (eg, China, India and Latin America). 25,27,28 In our cohort, almost all patients suffered local adverse events following vaccination with BCG; these included swelling or ulcerations >10 mm at the vaccination site. Seven patients developed BCGitis, which requires anti-tuberculosis therapy and highlights the key role played by CD40L-CD40 signalling in defence against tuberculosis infection.…”
Section: Discussionmentioning
confidence: 97%
“…(Table 3) We submitted the most deleterious 8 SNPs to project HOPE which revealed that all the SNPs are located in a domain in the protein and thus might have a vital change in the structure and function of the protein and it may affect its ability to bind with its targets. And we used Chimera software to visualize the amino acids change (figures [4][5][6][7][8][9][10][11] GeneMANIA revealed that CD40LG has many vital functions: adaptive immune response based on somatic recombination of immune receptors built from immunoglobulin superfamily domains, B cell activation, B cell activation involved in immune response, B cell proliferation, cell activation involved in immune response, cell-type specific apoptotic process, endothelial cell apoptotic process, inflammatory response, isotype switching, leukocyte activation involved in immune response, leukocyte mediated immunity, lymphocyte activation involved in immune response, lymphocyte proliferation, mononuclear cell proliferation, positive regulation of apoptotic process, positive regulation of cell death, positive regulation of cytokine production, positive regulation of programmed cell death, production of molecular mediator of immune response, regulation of endothelial cell apoptotic process, somatic diversification of immunoglobulins involved in immune response, somatic recombination of immunoglobulin gene segments, somatic recombination of immunoglobulin genes involved in immune response, tumor necrosis factor receptor superfamily binding. We also analysed the correlations between significantly regulated genes, share similar protein domain, or participate to achieve similar function were illustrated by GeneMANIA and shown in figure 3, Tables (4&5).…”
Section: Discussionmentioning
confidence: 99%
“…The X-linked hyper-immunoglobulin M syndrome (XHIGM) is a rare, inherited immune deficiency disorder. [1][2][3][4][5][6] autosomal recessive HIES (AR-HIES) is the most frequent form of the Hyper IgM syndrome which is characterized by elevated serum IgM levels and low to undetectable levels of serum IgG, IgA and IgE.. [7][8][9][10] it is more common in males. [10][11][12][13][14][15] Hyper-IgM syndrome is caused by mutations in the CD40LG gene.…”
Section: Introductionmentioning
confidence: 99%
“…This underscores the need to make PAP of unknown cause a trigger for immunological review. Congenital immunodeficiencies include agammaglobulinaemia [ 52 ], severe combined immunodeficiency secondary to adenosine deaminase deficiency [ 53 ], secondary haemophagocytic lymphohistiocytosis [ 54 ], infantile hypogammaglobulinaemia with heterozygous OAS1 mutations [ 55 ], hyper-IgM syndrome [ 56 , 57 ], and sporadic and autosomal dominant monocytopenia [ 58 ]. Bone marrow or stem cell transplant may be curative for some immunodeficiencies and specialist advice should always be sought [ 41 ].…”
Section: Aetiologymentioning
confidence: 99%